2014
DOI: 10.1007/s10545-014-9698-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hematopoietic stem cell transplantation on acyl‐CoA oxidase deficiency: a sibling comparison study

Abstract: Objective Acyl-CoA oxidase (ACOX1) deficiency is a rare disorder of peroxisomal very-long chain fatty acid oxidation. No reports detailing attempted treatment, longitudinal imaging, or neuropathology exist. We describe the natural history of clinical symptoms and brain imaging in two siblings with ACOX1 deficiency, including the younger sibling's response to allogeneic unrelated donor hematopoietic stem cell transplantation (HSCT). Methods We conducted retrospective chart review to obtain clinical history, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Unfortunately, as far as we know, follow up studies were not published on these patients. Hematopoietic stem cell transplantation was reported for one case of ACOX1 deficiency (neonatal adrenoleukodystrophy), but no information on hepatic parameters was provided and the patient died some years later from pneumonia without improvement in psychomotor development [142].…”
Section: Potential Treatments For Hepatic Peroxisome Pathologiesmentioning
confidence: 99%
“…Unfortunately, as far as we know, follow up studies were not published on these patients. Hematopoietic stem cell transplantation was reported for one case of ACOX1 deficiency (neonatal adrenoleukodystrophy), but no information on hepatic parameters was provided and the patient died some years later from pneumonia without improvement in psychomotor development [142].…”
Section: Potential Treatments For Hepatic Peroxisome Pathologiesmentioning
confidence: 99%
“…In addition to a delay in attaining early developmental milestones, almost all ACOX1-deficient children aged 24 to 48 months showed regression of motor achievements. Brain MRI studies demonstrated myelin loss starting in the white matter of the cerebellum, cerebellar peduncles and brainstem tracts, progressively extending to the midbrain and the cortical white matter (21,80,100,111,125,146,149).…”
Section: Acyl-coa Oxidase-1 Deficiencymentioning
confidence: 99%
“…Recently, it has been recognized that a proportion of patients with acyl‐CoA oxidase deficiency (ACOX1; OMIM 609751) may exhibit similar clinical, radiological and histopathological features to those of X‐ALD, especially in the cerebello‐brainstem form . Inherited deficiencies of peroxisomal straight chain VLCFA β‐oxidation include only X‐ALD and straight‐chain acyl‐CoA oxidase deficiency.…”
Section: Discussionmentioning
confidence: 99%